Kingdom of simplicity : a novel - Payne, Holly (Sausalito, [Calif.] : Skywriter Books, 2009)
Eli Yoder, a misguided Amish youth, after losing his family in a tragic accident, has struggled with forgiving the perpetrator. True to Amish tradition, everyone he knows has moved on with their lives except him. Shamed by his unwillingness to forgive, Eli leaves home during rumspringa, the time of 'running around' for Amish youth before they accept their faith, and searches for acceptance from the Outside World. Here a surprising friendship teaches Eli how to laugh again and prepares him to confront the biggest questions of his life.
Includes reading group guide.
Keywords: Amish -- Social life and customs -- Fiction; Rumspringa -- Fiction; Teenage boys -- Fiction; Forgiveness -- Fiction; Lancaster County (Pa.) -- Fiction